Dominica : Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on Dominica highlights economic developments and policies. Import growth has been robust on account of the economic recovery but the impact on the current account has been partially offset by increased tourism receipts. The efforts to reform the tax system and strengthen social security are necessary to place Dominica's public finances over the long term on a firmer footing.